1995
DOI: 10.2170/jjphysiol.45.979
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Contractile Properties of Extensor Digitorum Longus in Response to Creatine-Analogue Administration and/or Hindlimb Suspension in Rats.

Abstract: Changes of contractile properties of extensor digitorum longus in response to hindlimb suspension and/or altered high-energy phosphate contents were studied in rats. A reduction of high-energy phosphates, especially phosphocreatine, was seen in rats fed creatine analogue beta-guanidinopropionic acid (beta-GPA), but they were elevated after 10-d supplementation of creatine. The one-half relaxation time was increased by feeding beta-GPA, but was normalized by creatine supply. The fatigue resistance of creatine-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 0 publications
2
15
1
Order By: Relevance
“…Although Willoughby and Rosene [41] reported that long-term creatine supplementation increased muscle strength and size, possibly as a result of increased MHC synthesis, significant augmentation of the mechanical properties or hypertrophy was not observed by Stevenson and Dudley [42]. No beneficial effects of creatine loading were observed in our studies ( [8,9,11] and present results). In the present study, a single bout of swimming at two intensities was administered to the rats in each group.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Although Willoughby and Rosene [41] reported that long-term creatine supplementation increased muscle strength and size, possibly as a result of increased MHC synthesis, significant augmentation of the mechanical properties or hypertrophy was not observed by Stevenson and Dudley [42]. No beneficial effects of creatine loading were observed in our studies ( [8,9,11] and present results). In the present study, a single bout of swimming at two intensities was administered to the rats in each group.…”
Section: Discussioncontrasting
confidence: 72%
“…The administration of metabolic poisons such as 3Ј-azido-3Ј-deoxythymidine decreases the total activity of cytochrome oxidase in muscle [37], implying that ␤-GPA also may be a metabolic poison. However, the improved endurance swimming capacity observed in the current study and the increased fatigue resistance of the EDL muscle of ␤-GPA-fed rats, reported in a previous study [8], clearly indicate that the muscle oxidative capacity is not severely compromised. Furthermore, the total activity of SDH per CSA of muscle fiber, i.e., the ISDH, tended to be elevated, although the fiber size was decreased by ␤-GPA feeding, suggesting an increase in the specific activity of SDH.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…But the high-energy phosphate contents in the muscles were lowered. A similar reduction of high-energy phosphate contents in skeletal muscles was induced by feeding creatine analogue β-guanidinopropionic acid (β-GPA) to rats, and the fatigue resistance during swimming [5] or in response to the in situ electrical stimulation of skeletal muscle [6] was improved. These results suggest that the cold-exposure-associated improvement of fatigue resistance of skeletal muscles may be related to the metabolic stimulation caused by lowered high-energy phosphate levels.…”
mentioning
confidence: 91%
“…The fiber type composition of rat EDL muscle with improved fatigue resistance following β-GPA feeding was shifted toward a slow-twitch type relative to the controls [5,6]. Therefore, it is speculated that cold exposure, which causes the decrease of high-energy phosphate contents, may also result in the shift of fiber characteristics toward a slow-twitch type.…”
mentioning
confidence: 97%